Choice of dialysis modality: patients’ experiences and quality of decision after shared decision-making - Finderup, Jeanette; Lomborg, Kirsten; Jensen, Jens D; Stacey, Dawn (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Patients with kidney failure experience a complex decision on dialysis modality performed either at home or in hospital. The options have different levels of impact on their physical and psychological condition and social life. The purpose of this study was to evaluate the implementation of an intervention designed to achieve shared decision-making for dialysis choice. Specific objectives were: 1) to measure decision quality as indicated by patients’ knowledge, readiness and achieved preferences; and 2) to determine if patients experienced shared decision-making. Method A mixed methods descriptive study was conducted using both questionnaires and semi-structured interviews. Eligible participants were adults with kidney failure considering dialysis modality. The intervention, based on the Three-Talk model, consisted of a patient decision aid and decision coaching meetings provided by trained dialysis coordinators. The intervention was delivered to 349 patients as part of their clinical pathway of care. After the intervention, 148 participants completed the Shared Decision-Making Questionnaire and the Decision Quality Measurement, and 29 participants were interviewed. Concordance between knowledge, decision and preference was calculated to measure decision quality. Interview transcripts were analysed qualitatively. Results The participants obtained a mean score for shared decision-making of 86 out of 100. There was no significant difference between those choosing home- or hospital-based treatment (97 versus 83; p = 0.627). The participants obtained a knowledge score of 82% and a readiness score of 86%. Those choosing home-based treatment had higher knowledge score than those choosing hospital-based treatment (84% versus 75%; p = 0.006) but no significant difference on the readiness score (87% versus 84%; p = 0.908). Considering the chosen option and the knowledge score, 83% of the participants achieved a high-quality decision. No significant difference was found for decision quality between those choosing home- or hospital-based treatment (83% versus 83%; p = 0.935). Interview data informed the interpretation of these results. Conclusions Although there was no control group, over 80% of participants exposed to the intervention and responded to the surveys experienced shared decision-making and reached a high-quality decision. Both participants who chose home- and hospital-based treatment experienced the intervention as shared decision-making and made a high-quality decision. Qualitative findings supported the quantitative results. Trial registration The full trial protocol is available at ClinicalTrials. Gov ( NCT03868800 ). The study has been registered retrospectively.